Medidas ultrassonográficas de tempo, amplitude e velocidade do movimento do osso hioide durante a deglutição após tireoidectomia - Magalhães, Desiré Dominique Diniz de (2023)
Introduction: Thyroidectomy can negatively impact the movement of the hyoid bone (HO) during swallowing. Ultrasonography can analyze kinematic measurements of this event. Objective: 1) To synthesize the kinematic measurements of HO movement during swallowing, obtained by ultrasound in adults; 2) To compare the ultrasonographic measurements of time, amplitude and velocity of HO movement between patients sumitted and not submitted to thyroidectomy. Method: 1) Integrative literature review; 2) Cross-sectional study with analysis of 58 swallowing ultrasound records (liquid and thickened liquid, 10 mL each) of 29 individuals separated into an experimental group (EG - 12 people who submitted to thyroidectomy) and a comparison group (CG - 17 people without thyroid disease). Two trained speech therapists extracted and analyzed the measures independently, for comparison between groups. In the EG, measurements were also related to clinical characteristics. Results: 1) 26 articles were included, with great variability of objectives and methods. The most researched measures were movement, time and speed, the first being the most frequent. The levels of reliability and accuracy were little investigated. 2) Measurements were not different between groups. In the EG, the speed was significantly higher in individuals with swallowing complaints. Conclusion: 1) Time, amplitude and velocity was the kinematic measures of HO movement most investigated by ultrasonography, however, using different methods; 2) There is no difference in the measures evaluated between the groups. Individuals submitted to thyroidectomy have a higher speed of HO movement in the presence of a swallowing complaint.